Normal Variations and Pathologic Disorders of Chondrification and Ossification of the Foot and Related Diseases - Steinborn, Marc; Glaser, Christian (Seminars in Musculoskeletal Radiology, 2019)
Formation of the skeletal elements of the foot involves different stages of development. Failure in segmentation of the cartilaginous plate is supposed to be the underlying mechanism leading to tarsal coalition. Variants or disorders in ossification might result in harmless osseous anomalies or symptomatic disease. When the ossification is almost completed, several secondary ossification centers start to ossify. They are usually incidental findings. In symptomatic patients they have to be differentiated from fractures or can be the source of complaints by themselves.
Keywords: foot; variants; osteochondrosis; ossicles; coalition